The effect of using multimedia in teaching Arabic Language on developing reading comprehension skills among Primary School Student in Al-Jizah district - Alzaben, Hala Nawaf; Alassaf, Hamzeh Abdelfattah (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the effect of using multimedia in teaching Arabic Language on developing reading comprehension skills among Primary School Student in Al-Jizah district, The study employed a semi-experimental methodology. Data was collected using a reading comprehension test administered to a sample of 44 male and female fifth-grade students. The sample was divided into two groups: an experimental group of 22 students taught using multimedia, and a control group of 22 students taught using traditional methods, The study’s results indicated statistically significant differences, at a significant level, between the mean scores of the experimental group (taught using multimedia) and the control group (taught using traditional methods) in the post-test for reading comprehension skills. The experimental group outperformed the control group in terms of reading comprehension skills, In conclusion, the study suggests the importance of incorporating multimedia into Arabic language instruction due to its positive impact on the development of reading comprehension skills among primary school students.